دور التسويق الالكتروني في تدعيم الخدمات السياحية والفندقية - اكرام, بن مبروك; سناء, صوالح; مباركة, ودادة (University of eloued جامعة الوادي, 2020)
"إن الانتشار الواسع في استخدام تقنية تكنولوجيا المعلومات والاتصال تحولت من مجرد بيئة لتبادل المعلومات إلى أحد الركائز المهمة في مجال التسويق الالكتروني,حيث فتحت أفاقا واسعة في القطاع السياحي ,ويعد التسويق الالكتروني السياحي والفندقي الأداة الفعالة في رسم صورة سياحية جيدة من خلال عرض أهم الخدمات السياحية والفندقية بالاعتماد على تكنولوجيا المعلومات والاتصال ,حيث يتوقف نجاح المؤسسات السياحية والفندقية على توفر المعلومات اللازمة والجذابة القادرة على استقطاب أكبر عدد ممكن من الزبائن. و هدفت هذه الدراسة إلى التعرف على دور الذي يلعبه التسويق الالكتروني في تدعيم الخدمات السياحية والفندقية وتطويرها,ولتحيق هذا الهدف اعتمدت الدراسة على الأسلوب الوصفي لملائمته لطبيعة الدراسة ,حيث تم تصميم استبيان كأداة لجمع البيانات و توزعيه على عينة الدراسة والمتمثلة في مجموعة من الزبائن والبالغ عددها 60 استبانة, واستخدام الأدوات الإحصائية الملائمة،بالاعتماد على البرنامج الإحصائي Spssإصدار22 ,وقد توصلت الدراسة إلى وجود علاقة ذات دلالة إحصائية بين التسويق الالكتروني ودوره في تدعيم الخدمات السياحية والفندقية. ""The widespread use of information and communication technology has transformed from a mere environment for exchanging information to one of the important pillars in the field of electronic marketing, as it opened wide horizons in the tourism sector, and electronic tourism and hotel marketing is the effective tool in drawing a good tourism image by presenting the most important tourism services And hotels rely on information and communication technology, where the success of tourism and hotel establishments depends on the availability of the necessary and attractive information capable of attracting the largest possible number of customers. This study aimed to identify the role that electronic marketing plays in supporting and developing tourism and hotel services, and to achieve this goal, the study relied on the descriptive method for its suitability to the nature of the study, where a questionnaire was designed as a tool to collect data and it was distributed to the study sample represented by a group of customers, which are as many as 60 questionnaires, and the use of appropriate statistical tools, based on the statistical program SPPS version 22, and the study found a statistically significant relationship between electronic marketing and its role in strengthening tourism and hotel services. "
مذكرة تسويق فندقي
Keywords: التسويق الالكتروني السياحي و الفندقي ,الخدمات السياحية والفندقية; tourism and hotel electronic marketing, tourism and hotel services